Synthesis, Spectral, Powder X-Ray Diffraction and Antimicrobial Studies of Some Transition Metal(II) Complexes of Schiff Base Derived from 3-[(2-hydroxy-6- methylquinolin-3-ylmethylene)-amino]-2-methyl-3H-quinazoline-4-one - Siddappa, K.; Chandrakant Reddy, Patil; Kote, Mallikarjun; Reddy, Tukaram; Tambe, Mahesh; Metre, Mallikarjun (Asian Journal of Chemistry, 2011)
Complexes of the type ML2 and M′L [where, M = Cu(II), Co(II), Ni(II) and Mn(II); M′ = Zn(II), Cd(II) and Hg(II)] with the Schiff base L = 3-[(2-hydroxy-6-methylquinolin-3-ylmethylene)- amino]-2-methyl-3H-quinazoline-4-one, (HMQMAMQ) have been synthesized. Their characterizations have been done by elemental analysis, conductance data, magnetic susceptibility measurements, 1H NMR, electronic, IR, ESR and X-ray studies. Ligand field parameters of some of the complexes have also been calculated. On the basis of spectral studies, complexes of Co(II), Ni(II) and Mn(II) have been assigned octahedral geometry, where as the complexes of Zn(II), Cd(II) and Hg(II) have been assigned tetrahedral geometry. The complex of Cu(II) has been assigned distorted octahedral geometry. The ligand and its complexes have also been screened for their antimicrobial activity against selected fungi and bacteria.